Effects in Cognitive-Behavioral Intervention on Psychological Risk Factors of Cardiac Patients - Gorayeb, Ricardo (2015)
Reducing risk factors for cardiovascular diseases may increase quality of life and decrease mortality andmorbidity secondary to these disorders.The present study evaluated the efficacy of a cognitive-behavioral group intervention onanxiety, depression, stress and cardiovascular health of cardiac patients. Ninety-one patients were assessed before and after thegroup intervention by means of semi-structured interviews, the Beck Anxiety and Depression Inventories and the Lipp’s StressSymptoms Inventory for Adults. Cardiovascular status was estimated using the Framingham Score. The intervention decreasedanxiety, depression, and stress, and improved coping with stress. No significant differences were seen for the FraminghamScores. The intervention was effective in improving psychological risk factors for the investigated sample.